2009
DOI: 10.1097/01.tgr.0000346058.32801.95
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning From Driving to Driving Cessation

Abstract: Introduction:Because of the saliency of driving, loss of driving privileges often is very difficult for individuals with a dementia and an ongoing and emotional stressor for caregivers/other family members. Despite this loss, few community-based interventions exist to assist individuals with a dementia and their family members, with the driving cessation process. Objective: To assess the effectiveness of theoretical group interventions associated with loss of driving privileges for individuals with dementia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…There is beginning evidence that support groups are effective in helping individuals with dementia and their caregivers address and adjust to driving cessation. One study found that engaging in a formal driving support group after the loss of a driver's license helped individuals with AD cope with the transition (Dobbs et al, 2009). In addition, supporting caregivers with a psycho-education group class specifically focused on driving cessation may improve their ability to address and cope with driving cessation with their loved ones with dementia (Stern et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is beginning evidence that support groups are effective in helping individuals with dementia and their caregivers address and adjust to driving cessation. One study found that engaging in a formal driving support group after the loss of a driver's license helped individuals with AD cope with the transition (Dobbs et al, 2009). In addition, supporting caregivers with a psycho-education group class specifically focused on driving cessation may improve their ability to address and cope with driving cessation with their loved ones with dementia (Stern et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies examined the effect of support groups on adjustment to driving cessation. Dobbs, Harper, and Wood (2009) investigated the benefit of two types of support groups (driving cessation-specific support group versus general AD support group) for individuals with early-stage dementia who had their drivers' license revoked. Although all participants rated the support groups as helpful, the findings supported the driving cessationspecific support group as better at equipping participants to cope with the loss of their driving privileges.…”
Section: Interventions For Driving and Driving Cessationmentioning
confidence: 99%
“…Investigation of driving cessation issues for people with dementia has highlighted similar losses (Jett et al, 2005). People with dementia are also noted to have restricted options in terms of transportation without driving (Perkinson et al, 2005;Dobbs et al, 2009). People with dementia are also noted to have restricted options in terms of transportation without driving (Perkinson et al, 2005;Dobbs et al, 2009).…”
mentioning
confidence: 99%
“…Mobilizing family and community support and adequate follow up are strategies that can ensure a successful transition. Work by Dobbs et al [18] has shown that driving cessation groups designed to assist in the driving retirement process can mitigate the negative consequences of losing one’s driving privileges. Framing driving as a health issue and not a “taboo” topic can assist in shifting the focus from age to risk factors.…”
Section: Scope Of the Problemmentioning
confidence: 99%
“…using various measures. [18] Changes in driving identity may require negotiation and acceptance over time, with family input and sensitivity [7]. …”
Section: Scope Of the Problemmentioning
confidence: 99%